INTEGRATED HOME AUTO IRRIGATION SYSTEM USING MOBILE APPLICATION - Abdul Ghani, Muhd Azwan (IRC, 2019)
This project presents the integrated home auto irrigation system using mobile application to control the water pump remotely and irrigate the plant automatically using soil moisture sensing. Auto irrigation system is good for the growth of the plants. However, it is challenging to maintain the accuracy of the soil moisture level, monitor the sensors value and maintain an optimum amount of water based on plant’s need when the people are going away from home. The components were first programmed separately before integrated as one system. The main component of the system is Arduino Board. The experiment is carried out between commercialized soil moisture sensor and galvanized steel using compost soil with different volume of water. The soil moisture level was measured to compare the analog reading between the two probes. The reading between the two probes is almost similar. Besides, the galvanized steel also able to maintain the accuracy of the soil moisture level for a long time compare commercialized soil moisture sensor which easily corroded after two months and effect the accuracy of the soil moisture level. The details of the system based on previous project and research are included together in this paper.